Determination of interdiffusion coefficients of Si and Al in Ti3SiC2–Ti3AlC2 diffusion couple at 1373‐1673 K. Issue 1 (27th August 2019) - Zhang, Zerong; Yin, Xiaohui; Qian, Yuhai; Xu, Jingjun; Zuo, Jun; Li, Meishuan
Abstract: In the diffusion couple of Ti3 SiC2 and Ti3 AlC2, only interdiffusion of Si and Al occurred during diffusion treatment process. Based on the concentration profiles of Si and Al measured by electron probe microanalysis (EPMA), the interdiffusion coefficients of Si and Al at 1373‐1673 K in Ti3 SiC2 –Ti3 AlC2 diffusion couple were determined by both the Boltzmann‐Matano (B‐M) method and the Saucer‐Freise (S‐F) method. At the position of Matano plane with the composition of Ti3 Al0.5 Si0.5 C2, the interdiffusion coefficient could be expressed as D int (m 2 /s) = 5.6 × 10 −4 ⋅exp [−246 ± 14 (kJ/mol)/RT]. Based on the two methods, the calculated interdiffusion coefficients increased with increasing temperature, and the magnitudes of their absolute values were on the order of 10 –13 ‐10 –11  m 2 /s at 1373‐1673 K. At 1373‐1573 K, the calculated interdiffusion coefficients decreased monotonously with the increase of Si concentration, that is, x Si /( x Al  +  x Si ). But at 1673 K, the variation trend of interdiffusion coefficients with x Si /( x Al  +  x Si ) was no longer monotonous, probably due to the presence of Ti5 Si3 phase and voids on Ti3 AlC2 side.